2007
DOI: 10.1002/ijc.22363
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of estrogen‐related receptor α (ERRα) is a negative prognostic predictor in human prostate cancer

Abstract: The nuclear receptor ERRα (estrogen‐related receptor α) is known to modulate the estrogen‐signaling pathway, but the biological significance of ERRα in the prostate remains unclear. We investigated the expression of ERRα in human prostate tissues and cancer cell lines to evaluate the potential roles of the receptor in prostate cancer (PC). Western blot analysis of ERRα was performed in three cell lines of human PC (LNCaP, DU145 and PC‐3). The expressions of ERRα in cancerous lesions (n = 106) and benign foci (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
73
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 37 publications
(68 reference statements)
3
73
0
2
Order By: Relevance
“…Furthermore, ESRRA is up-regulated in several cancers, such as tumors of the breast, colorectum, prostate, and ovary (4 -8), reinforcing its potential role in tumorigenesis. More importantly, an increased level of ESRRA is linked to poor prognosis of breast, ovarian, and prostate tumors (7,9,10). Several reports suggest that the pharmacological modulation of ESRRA activity with specific inverse agonists such as XCT790 reduces proliferation of cell lines derived from breast, glial, lung, and cervical tumors (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Furthermore, ESRRA is up-regulated in several cancers, such as tumors of the breast, colorectum, prostate, and ovary (4 -8), reinforcing its potential role in tumorigenesis. More importantly, an increased level of ESRRA is linked to poor prognosis of breast, ovarian, and prostate tumors (7,9,10). Several reports suggest that the pharmacological modulation of ESRRA activity with specific inverse agonists such as XCT790 reduces proliferation of cell lines derived from breast, glial, lung, and cervical tumors (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Elevated ERRα expression in cancerous lesions was significantly correlated with poor cancer-specific survival rates in patients with prostate cancer (21). In human breast carcinoma, ERRα immunoreactivity was significantly associated with increased recurrence and shorter survival times (22).…”
Section: Errα Expression (N=128) ------------------------------------mentioning
confidence: 97%
“…Overall survival Disease-free survival of immunohistochemistry on prostate cancer specimens, researchers demonstrated that nuclear ERRα expression was significantly higher in the cancerous lesions compared with that in benign epithelia (21). Elevated ERRα expression in cancerous lesions was significantly correlated with poor cancer-specific survival rates in patients with prostate cancer (21).…”
Section: Errα Expression (N=128) ------------------------------------mentioning
confidence: 99%
“…Of the three subtypes, ERRα and ERRγ are the most consistently and prominently expressed in prostate cancer cells, tissue and xenografts at both RNA and protein levels; although ERRβ expression is high in normal prostate tissue, but lost in cancer (Cheung et al 2005). Expression of ERRα is inversely associated with prostate cancer outcome: in a cohort of 106 patients, ERRα expression increased in cancer compared with that in BPH and was significantly associated with poor prostate cancer-specific survival (Fujimura et al 2007). Consequently, ERRα has been reported to be pro-proliferative (Bianco et al 2009) whilst also providing protection against hypoxia (Zou et al 2014), and increasing prostate cancer cell invasiveness (Tribollet et al 2016).…”
Section: Oestrogen-related Receptors (Errα/β/γ or Esrr α/β/γ Or Nr3b1mentioning
confidence: 99%